Relationship of Work-Family Conflict, Work Motivation and Social Support to ASN Women's Performance in East Java Province Government Organization. - Satriawan Wicaksono (Eximia, 2021)
This study aims to determine the relationship of work-family conflict, work motivation, and social support to the performance of ASN women in the East Java provincial government organization. This study uses a quantitative approach. The study was conducted in two stages, namely the initial stage in the form of a validity and reliability test questionnaire then continued with the implementation stage in the form of questionnaire distribution. The population in this study was ASN Wanita in East Java provincial government organizations, a sample of 110 people. The analytical tool used in this study uses Structural Equation Modeling (SEM) with AMOS 22 software. The results showed that there was a significant influence of work-family conflict on performance, work-family conflict on work motivation, work motivation on performance, social support on work-family conflict, social support on work motivation but there was no significant effect between social support and the performance.